Pengaruh Kepemimpinan Visioner, Motivasi, dan Kompetensi terhadap Budaya Kerja dan Komitmen serta Implikasinya pada Kinerja Dosen - Sahat Simbolon (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2017)
The aim of this research purpose is to know, to analyze and review (1) visionary leadership, work motivation, lecturer’s competency, work culture, work commitment and lecturer’s performance, (2) The great of influence contribution visionary leadership, work motivation, lecturer’s competency toward work culture and work commitment, (3) The great of influence contribution work culture and commitment toward lecturer’s performance. This research was conducted using descriptive methods and verifycative. The sampling technique used cluster random sampling, with population as much 3.412 lecturer’s and sample number as much 251 respondents. The research has conducted on private colleges in Medan North Sumatera Province. The analysis tool used is the Path Analysis with its calculation use SPSS 20. This research result has shown that: (1) Condition visionary leadership, work motivation, lecturer competency, work culture, work commitment states in high category, except lecture performance in high enough category. (2). Relation closeness of independent variable X1 with X2, and X2 with X3 are having strong relation level, variable X1 with X3 are having strong enough relation level. While highest relation closeness as much 0.652 for variable X1 and X2, and lowering as much 0.514 for variable X1 and X3. Intervening variable relation closeness Y1 with Y2, having stronger relation level that is 0.991. (3). There is significant influence relation from all of independent variables toward work culture, with influence number as much 64.7%. (4). There is significant influence from all of independent variables toward work commitment, with influence number as much 61.3%. (5). There is significant influence from all of intervening variables toward lecture performance, with influence number as much 87.6%.